Literature Survey on IDS of MANET (International Journal of Scientific Research and Management (IJSRM), 2015)
Mobile Ad hoc Networks (MANETs) are multi hop wireless networks, in which nodes move and communicate with each other without any centralized control or base stations. Due to its mobile nature topology of network changes frequently so it is a challenging task to provide an efficient and effective routing in MANETs with limited resources. As MANET is open medium, various attackers can attack the network. Due to node’s physical protection, malicious attackers can easily attack the nodes. To avoid such attacks a good intrusion detection and prevention systems were developed. This Literature paper gives a brief survey about different IDS developed to protect attacks in MANET and strengthen its security